Distance Education, remote teaching and new educational information and communication technologies in a pre and post-pandemic scenario (Research, Society and Development, 2020)
One of the first measures in mid-2020, was the immediate suspension of face-to-face activities in educational institutions spread across various parts of the world as a way of maintaining social distance and preventing the spread of the virus, as soon as the public health emergency broke out due to the spread of the new coronavirus (COVID-19). Because of the decree of the new ordinances of the Ministry of Education and Health, there was an orientation and at the same time permission, in the sense that educational institutions throughout the country, use remote methodologies to continue the school year. Among the segments of transformation, education needed to adapt radically to these resources. This reality demanded from education professionals skills hitherto not mandatory. In this scenario, the objective of the present study is to analyze the implications of these measures concerning the large-scale adoption of “remote education” as a substitute for face-to-face activities and the use of new information and communication technologies in this process, including in the post-pandemic. For this, the method used was of qualitative nature of the bibliographic type with a literature review on materials already published online. The gift study suggests that new technologies, even though they are essential for the new world panorama, need, above all, more adaptation of both students and teachers to become unanimously efficient technologies in the teaching-learning aspect.